Perceived Postgraduate Research Supervisory Practices and Satisfaction towards Supervision among Supervisees at Faculty of Education - Ishak, Nurhamizah; Khairuddin, Farah Nadzirah; Aziz, Nur Shaziella (IIUM Journal of Educational Studies, 2021)
Effective supervision received by postgraduate students boosts their motivation to produce a high quality research. This paper looks at the perceived postgraduate research supervisory practices and satisfaction towards supervision among supervisees at Faculty of Education in a Malaysian public university. Data was collected through a questionnaire on the sample of 45 Part 3 full-time Master’s degree (Coursework) students. However, only 33 sets of questionnaires were returned to the researchers (response rate=94.3%). It was found that most supervisees perceived that their dissertation supervisors have continually applied various supervisory practices during the supervision session and they were very satisfied with the supervision that they have received. Furthermore, there was a positive, strong, and significant relationship between the perceived supervisory practices and supervisees’ satisfaction. Nevertheless, there were no significant differences between perceived supervisory practices and courses, as well as between perceived supervisory practices and frequency of meeting. As for the implications of this study, it contributes to the corpus of knowledge in the area of postgraduate supervision in local higher education institution context and provides empirical data to assist the Ministry of Education in conducting strategic planning to enhance implementation of effective supervisory practices among postgraduate research supervisors.